Enhanced Eastern Pacific Warming Weakens ENSO Asymmetry Post‐2100 Under Persistent Greenhouse Warming - Tao Geng; Wenju Cai (Geophysical Research Letters, 2025)
Abstract The El Niño‐Southern Oscillation (ENSO) exhibits a strong amplitude asymmetry between El Niño and La Niña, in which establishment of atmospheric convection in the climatologically cold and dry eastern Pacific provides a major source of nonlinearity. Under greenhouse warming, ENSO is projected to strengthen pre‐2100 and weaken thereafter, but how ENSO asymmetry may change is unclear. Here we show that despite a muted change in the 21st century, ENSO amplitude asymmetry in sea surface temperature (SST) weakens substantially post‐2100 under persistent greenhouse warming. In a warming climate beyond 2100, the eastern Pacific continues to warm faster than the surrounding regions, pushing SSTs above the convective threshold. A wetter background favors a larger rainfall reduction in response to cold SST anomalies, thereby diminishing the nonlinearity of convective response and associated coupled feedbacks with respect to El Niño and La Niña. Such changes are absent under low‐emission scenarios when the eastern‐Pacific warming ceases after 2100.